Diagnosis and environmental planning for Paranagud - PR - Brazil - Lautert, L. F.; Sa, F.; Machado, E.; Brandini, N.; Marone, E.; Noernberg, M. A.; Mauro, C. [UNESP] (Coastal Education & Research Foundation, 2006)
The main goal of this study was to identify and analyse environmental problems related to human occupation at the south part of the city of Paranagua PR, Brazil, aiming the diagnosis and conceptual evaluation of landscape use. For landscape use assessments and degradation diagnosis purposes, the environment was classified considering mainly geological and geomorphologic characteristics, such as declivity and sediment origin. The identification of potential environmental impacts was made by aerial photographs, Landsat-TM images, photographic records, surface sediment samples, water-column samples, and mainly observation visits to each classified unit. Surface sediment samples were taken with a Petit-Ponar sampler, in 13 station located in Paranagua Bay. In order to characterize the contamination level on sediments, the concentration of the following elements were analysed: arsenic (As), copper (Cu), cadmium (Cd), nickel (Ni), lead (Ph) e zinc (Zn). For the extraction of these elements, samples were treated with HCl 0.1N for 12 hours. This method has the advantage of determining contaminants which are weakly bind to the sediment, thus more available to the system. Analysis were performed by atomic absorption spectroscopy. According to the adopted criteria, sectors were classified as hills, mangroves, continental sediments and beach ridges urban and port industrial. Water quality and concentrations of metallic elements were determined at three sectors one control and two with the influence of urban and port/industrial activities, respectively the major upland impacts found were: deforestation due to disordered occupation, and solid waste emission through domestic and industrial sewage. The diagnosis of the actual situation was used as a basis for a management plan, once it allows the identification of impacts, and consequent environmental irregularities. Based on this considerations, suggestions for land use and management were presented, which offers a better approach for recuperation and protection of the studied ecosystem.
Keywords: port/industrial activities